Climate change and food security: Assessing the prospect for Kuwait using an economy-wide model: DOI: 10.48129/kjs.15943 - Gelan, Ayele; Atkinson, Giles (Kuwait Journal of Science, 2022)
This study is concerned with food security effects of climate change and global warming in Kuwait. The Intergovernmental Panel on Climate Change (IPCC) has a system of monitoring the impacts of human activities on climate change and global warming has essentially remained a top-down and falls out of favour among end user communities. The needs of policymakers at national scale have remained peripherals. Kuwait’s food security is a good case to illustrate the fact that the IPCCs global scenarios are far removed from the concerns of national policymaking at national scale. The study is implemented by applying a recursive dynamic computable general equilibrium (CGE) model for Kuwait and calibrating it on Kuwaiti data to examine food security impacts of the five IPCC’s Shared Socio-economic Pathways (SSP). The Kuwaiti national model is softly linked to the global model by constructing a world food price index (WPI) from global excess demand for food. The simulation results indicated asymmetrical impacts of IPCC’s SSP on Kuwait’s agriculture and food processing industries. The “high growth scenario” or the “busines as usual scenario” is associated with maximum food price increase in the world market in the long run. This favours primary food production because agricultural production becomes feasible. The “sustainability scenario”, strict enforcements of global climate change policies, leads to the lowest global food price increase in the long run. This favours the food-processing sector since low world market price means food-processing industries will get cheap imports for further processing. IPCC models have little to offer in explaining food security impacts in already arid and heavily food import dependent countries like Kuwait. These countries would greatly benefit by enhancing national capacities that consider specific country circumstances to assess food security implications of global warming scenarios.